Ivory towers? The commercial activity of British professors of engineering and physics, 1880–1914. (2nd January 2017) - Guagnini, Anna
Abstract: The involvement of British academic scientists in commercial work has been often discussed by historians of science and technology. However a systematic study of this activity is still lacking. Focussing on the period 1880 to 1914, I examine the engagement in consulting, patenting and entrepreneurial initiatives of a segment of that community, namely engineering and physics professors. I discuss the institutional context in which it occurred and their motivations. The survey highlights that the majority of the engineering professors examined were involved in consulting and patenting, and a significant number of them pursued also entrepreneurial activities. As for the physics professors, only a few followed the example of their engineering colleagues, but did so vigorously. I argue that far from being reluctantly brought into the market for knowledge, the engineering as well as the physics professors who engaged these extra-academic activities eagerly sought to partake in the commercialization of the products of their scientific work.